How the Primer-Literate Read Ming Steles: A Digital Speculation. Issue 1 (January 2020) - Schneewind, Sarah
Abstract: Historians disagree about the role of literacy in Ming society. Certainly, the stone inscriptions that littered the Chinese landscape displayed elaborate essays showing the gentry author's erudition and compositional skill. Yet steles for shrines to living officials also sent political messages. They authorized and amplified the voice of "the common people, " embodying and explicitly arguing for a popular voice in the evaluation of magistrates and prefects. How were these texts on public monuments understood by the many Ming people with only basic literacy? The Late Imperial Primer Literacy Sieve is a digital tool that sifts a target text, such as a commemorative stele, leaving only the characters found in one or more primers. The Sieve may bring us closer to understanding not only what was written, but what was read. The article argues that the message of premortem steles about popular participation could indeed come across.